2012
DOI: 10.5539/ijbm.v7n12p173
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Psychological Distance in Tourism Marketing

Abstract: International tourism has emerged as an important earner industry for a country's economy. It has a significant position in national economic development and needs a continuous evaluation. To do so, it is imperative to understand the dynamics of global tourists' behaviours, perceptions and the ways that tourists evaluate their destinations. The present research endeavours to consider the application of psychological distance in tourism marketing. Psychological distance has been applied in marketing research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Also, Hofstede's (1980) four cultural dimensions were extracted on the basis of work-related values. Some research suggested that it should be modified for tourism application (Abooali & Mohamed, 2012). Despite of these concerns, Hofstede's study has some appealing attributes.…”
Section: Limitation and Future Research Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Hofstede's (1980) four cultural dimensions were extracted on the basis of work-related values. Some research suggested that it should be modified for tourism application (Abooali & Mohamed, 2012). Despite of these concerns, Hofstede's study has some appealing attributes.…”
Section: Limitation and Future Research Directionmentioning
confidence: 99%
“…Shenkar (2001) argued that the perceptual component of cultural distance has been largely ignored. In marketing-related research, psychic distance was introduced to detect cultural distance at individual level (Abooali & Mohamed, 2012 …”
Section: Limitation and Future Research Directionmentioning
confidence: 99%
“…A growing body of tourism research also suggests that similarity–dissimilarity is an important factor in destination choice. Most of this research has focused on whether cultural similarity between a tourist’s home country and an international destination increases the likelihood of travel to that destination (e.g., Abooali & Mohamed, 2012; Bi & Lehto, 2018; Ng et al, 2007). This research has produced somewhat mixed results.…”
Section: Literature Reviewmentioning
confidence: 99%